2021
DOI: 10.1038/s41416-021-01367-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of geriatric intervention in frail older patients receiving chemotherapy for colorectal cancer: a randomised trial (GERICO)

Abstract: Background Older patients with colorectal cancer (CRC) experience chemotherapy dose reductions or discontinuation. Comprehensive geriatric assessment (CGA) predicts survival and chemotherapy completion in patients with cancer, but the benefit of geriatric interventions remains unexplored. Methods The GERICO study is a randomised Phase 3 trial including patients ≥70 years receiving adjuvant or first-line palliative chemotherapy for CRC. Vulnerable patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 61 publications
(58 reference statements)
2
91
3
4
Order By: Relevance
“…Currently, few RCT studies have examined the effects of CGA in older patients with various cancer sites receiving antineoplastic treatment. Only one of these studies specifically screened for frailty using the G8, though exclusively included patients with colorectal cancer stage II-IV [27]. This study showed a positive effect of receiving CGA on chemotherapy treatment completion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, few RCT studies have examined the effects of CGA in older patients with various cancer sites receiving antineoplastic treatment. Only one of these studies specifically screened for frailty using the G8, though exclusively included patients with colorectal cancer stage II-IV [27]. This study showed a positive effect of receiving CGA on chemotherapy treatment completion.…”
Section: Discussionmentioning
confidence: 99%
“…The G8 is based on the Mini Nutritional Assessment, with scores ranging from 0 to 17 and a cut-off for frailty at G8 ≤ 14 [24]. The G8 has previously been applied in several Danish studies, with percentages of G8 frailty in older patients with cancer ranging from 50 to 72% [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our trial addresses a critical gap regarding the effectiveness of geriatrics-driven interventions in older patients with hematologic malignancies, complementing emerging evidence from other studies predominantly consisting of older adults with solid tumors. [15][16][17][27][28][29][30][31] Few prior studies have investigated GA-driven interventions for patients with blood cancers. Artz and colleagues recently reported that in patients with a median age of 67 undergoing hematopoietic stem cell transplantation for blood cancers, GA-driven interventions implemented by a multidisciplinary geriatrics team improved 1-year overall survival in comparison with conducting a GA alone without a multidisciplinary team to manage any detected vulnerabilities.…”
Section: Discussionmentioning
confidence: 99%
“…GA has been demonstrated to alter the initial oncology treatment plan in at least a quarter of patients (median 28%; range 8-54%), with non-oncological interventions being recommended in almost three-quarters of patients (median 72%; range 26-100%) [15]. Recent randomized controlled trials demonstrated improvements in quality of life, unplanned hospital admissions, and reduced chemotherapy toxicity and early treatment discontinuation, confirming the importance of GA in older cancer patients [16][17][18][19]. In addition, several Oncological Societies internationally have published guidelines on GA, which include recommendations for cognitive assessment or screening [1,[20][21][22].…”
Section: Introductionmentioning
confidence: 93%